In early rheumatoid arthritis, comorbidities do not explain the increased risk of failure to reach remission in patients with obesity - Johan Askling; Lars Klareskog; Lars Alfredsson; Saedis Saevarsdottir; Helga Westerlind; Bénédicte Delcoigne; Liselotte Tidblad; Anton Öberg Sysojev (RMD Open)
Objective To examine whether obesity and/or overweight are independently associated with an increased risk of remission failure in patients with early rheumatoid arthritis (RA), treated with methotrexate as first disease-modifying antirheumatic drug, or if the previously reported associations could be explained by underlying comorbidities and lifestyle factors.Methods For patients included in the Epidemiological Investigation of Rheumatoid Arthritis (EIRA) study 2006–2018 initiating methotrexate monotherapy (n=1285), we captured data on body mass index, comorbidities and disease activity from EIRA and through linkage to nationwide Swedish clinical and quality registers. The primary outcome was failure to reach 28-joint Disease Activity Score (DAS28) remission at 3 and 6 months. Secondary outcomes included Boolean, Simplified Disease Activity Index and Clinical Disease Activity Index remission and their individual components. We estimated the relative risk (RR) of remission failure in patients with obesity and overweight compared with normal weight using modified Poisson regression, adjusting for potential confounders.Results After 6 months, 64% (n=98/153) of patients with obesity, 52% (n=171/326) with overweight and 48% (n=210/433) with normal weight failed to reach DAS28 remission, with an RR of 1.33 (95% CI 1.14 to 1.55) for patients with obesity after adjustment for age and sex. The increased risk of remission failure in patients with obesity remained after further adjustment for seropositivity, educational level, smoking, alcohol use, physical activity, calendar period, glucocorticoid treatment and comorbidities (RR=1.27, 95% CI 1.08 to 1.50). No significant association was observed for patients with overweight. The results were similar for the secondary outcomes and after 3 months.Conclusion Obesity is a risk factor for remission failure in early RA, independent of comorbid conditions.